TRAVEL BEHAVIUOR OF WOMEN TO MARKETS IN RURAL COMMUNITIES IN AYEDAADE LOCAL GOVERNMENT AREA OF OSUN STATE - Adetunji, Musilimu Adeyinka (Journal Economics & Business Atmajaya Indonesia, 2020)
This study examined the accessibility of women to markets in some rural communities in Ayedaade Local Government Area of Osun State. Both primary and secondary data were utilised for this research. Three sets of data were required. The first set of data focused on the socio-economic characteristics of rural dwellers with emphasis on gender composition, level of education and possession of personal means of transportation. The second data required focused on the travel pattern of rural population to markets taking into account attributes such as distance travelled, mode of transportation mostly used, average travel time and frequency of trip to market in a week. The last category of data elicited was based on constraint of women to access market centres in the region. Descriptive and inferential statistics were employed to analyse the data. Findings reveal that agricultural products and few manufactured goods are traded at Olufi central market in the study area. More than 60% of women relied on public transport services to convey their goods to markets. 30% of women in the rural communities trekked to markets and travelled several kilometres to engage in commercial activities. There is gender variation on transport mode to markets in the rural region of Ayedaade Local Government. Many of the rural population claimed that their agricultural produce decayed on transit because of infrequent operation of the transport services in the region. The study therefore recommends that there is need to provide community based transport services at subsidized rate for rural communities in Nigeria so as to enhance the accessibility of women to markets and participate in other productive activities in the rural areas of Nigeria.